Metaphor as a cognitive and relational tool for self-narrating experience of addiction: a qualitative-quantitative analysis - Altavilla, Daniela; Mazzaggio, Greta; Deriu, Valentina; Garello, Stefana; Vecchi, Alessia; Adornetti, Ines; Chiera, Alessandra; Canali, Stefano; Ferretti, Francesco (Frontiers in Psychology, 2025)
IntroductionMetaphors have been acknowledged as crucial for understanding and articulating complex experiences, helping individuals make sense of emotional and social challenges, especially during tough times. In the context of addiction, previous studies have highlighted the potential of metaphorical language to facilitate the expression and comprehension of emotions related to addictive behaviors. However, little research has explored when and what types of metaphors people use in their personal stories about addiction. Aim of current study was to address this gap by analyzing metaphorical language in self-narratives of individuals with addiction.MethodsSixty-three participants (37 men and 26 women; age range: 18–65 years) undergoing treatment at public addiction services were recruited. Self-narratives were elicited through a semi-structured interview covering eight addiction-related topics: aspecific desire, definition of addiction, onset of addiction, specific desire/craving, loss of control, relationships with the environment, relapses, and future self-projection. The occurrence of seven metaphorical clusters was identified and quantified: structural, personification, split-self, bodily, movement, ontological, and idiomatic metaphors.ResultsThe main findings showed a significantly higher frequency of metaphor use in the definition of addiction compared to all other thematic areas. Moreover, ontological and movement metaphors were especially prevalent in narratives addressing the definition and onset of addiction.DiscussionThese results highlight how individuals with addictive disorders tend to concretize their experience through specific methaphorical patterns—particularly, ontological and movement metaphors. Overall, the use of these metaphor forms appears to provide emotional containment and representational clarity, enabling individuals to express their inner conflicts and emotional ambivalence associated with addiction.